Ulotne duchy Indianie w poezji Philipa Freneau i Williama Cullena Bryanta a koncepcje rasowe dziewiętnastowiecznej nauki - Fruzińska, Justyna (Strategie komunikacyjne i procesy twórcze, 2022)
The paper analyzes the depiction of Native Americans in poems by two 19th-century American poets: Philip Freneau and William Cullen Bryant. Romantic writers were interested in Native Americans as “noble savages,” but also as a metonymy of “natural” America as opposed to “civilized” Europe. The poets often took the side of the Native population, mistreated and pushed westward by whites, both for ethical and esthetic reasons: appreciating their “picturesqueness” and nostalgically describing cultures which no longer constituted a military threat on the eastern shore of the United States. At the same time, however, their attitudes towards Native Americans could be far more complicated, as one can see in Bryant’s poem “The Prairies,” which de facto justified the US Indian policy of the 1830s. What is more, both poets’ works largely reflected racial ideas dominating 19th-century science. The poems which this paper analyzes refer to the motif of the “dying American,” doomed to extinction because of his physical weakness and unwillingness to accept white civilization, as well as the enigma of the “mound builders,” which intrigued many 19th-century scientists and was taken up by Bryant in his “Prairies.”